The Arabidopsis TIRome informs the design of artificial TIR (Toll/interleukin-1 receptor) domain proteins - Adam M. Bayless; Lijiang Song; Mitchell Sorbello; Sam C. Ogden; Tyler S. Todd; Alice Flint; Natsumi Maruta; Jedidiah Tulu; Mikhail Drenichev; Vardis Ntoukakis; Thomas Ve; Mehdi Mobli; et al. (Proceedings of the National Academy of Sciences, 2025)
The TIR (Toll/interleukin-1 receptor) domain is an ancient protein module that functions in immune and cell death responses across the Tree of Life. TIR domains encoded by plants and prokaryotes function as enzymes to produce diverse small molecule immune signals. Plant genomes can encode hundreds of TIR-domain containing proteins—many of which confer important agricultural disease resistance as TIR-NLR (nucleotide-binding, leucine-rich repeat) immune receptors. Despite their importance, how natural variation influences TIR enzymatic output and immunity-associated cell death is largely unexplored. We assayed a complete collection of the TIR domains of Arabidopsis thaliana Col-0 (the “AtTIRome”) to explore variation in TIR metabolite production and cell death signaling. Roughly half of the AtTIRome triggered cell death in transient assays. Artificial TIR proteins designed based on consensus sequences of the AtTIRome’s cell death phenotypic classes revealed polymorphisms controlling variation in TIR cell death elicitation and metabolite production. Structure–function analyses of artificial TIRs revealed that natural variation in the “BB-loop”, a flexible region overlying the catalytic pocket, determines differences in function across Arabidopsis TIR-containing proteins. We further demonstrate that artificial TIRs are functional on an NLR chassis and that BB-loop variation can tune the activity of a natural TIR-NLR protein. These findings shed light on the diversity of TIR outputs and reveal methods to design and engineer TIR-based immune receptors.